Errare, sviarsi, vagabondare lungo il sentiero della traduzione letteraria (Altre Modernità, 2017)
The essay intends to look at the notion of error with particular reference to literary translation from English into Italian. It specifically focuses on texts uncomfortably poised between spoken and written language, coming from postcolonial literature written in contact languages (Nigerian Pidgin English and rotten English), and American literature written in dialects and vernaculars. It will try to shed light on how the norm/usage dichotomy can be creatively explored and redefined by both the writer and the translator.